2019
DOI: 10.1088/1757-899x/535/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Improving the compact crucible furnace performance by adding fins in heating chamber

Abstract: A crucible furnace is developed continuously to obtain appropriate furnace in support casting practice at VHS. This research aimed at improving performance of compact crucible furnace by modification the heating chamber. Fins were placed at inner side of compact crucible furnace wall. The furnace performance determined by increasing of temperature rate to melt 3 kg of aluminium. Descriptive analysis is used to describe performance of modified compact crucible furnace. The fins addition on the inside wall impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In addition to start the casting, types of stoves and fuels have been studied such as the use of crucible furnace heated by Liquid Petroleum Gas (LPG) in melting the aluminum metals at 600 o C [4][5][6][7] and. It also has been reported that a furnace supported by kerosene was able to melt aluminum metals with 30 Kg of capacity [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to start the casting, types of stoves and fuels have been studied such as the use of crucible furnace heated by Liquid Petroleum Gas (LPG) in melting the aluminum metals at 600 o C [4][5][6][7] and. It also has been reported that a furnace supported by kerosene was able to melt aluminum metals with 30 Kg of capacity [8].…”
Section: Introductionmentioning
confidence: 99%